Beneficial Effect of Alcohol Withdrawal on Gut Permeability and Microbial Translocation in Patients with Alcohol Use Disorder. (22nd November 2017) - Donnadieu‐Rigole, Hélène; Pansu, Nathalie; Mura, Thibault; Pelletier, Stéphanie; Alarcon, Régis; Gamon, Lucie; Perney, Pascal; Apparailly, Florence; Lavigne, Jean‐Philippe; Dunyach‐Remy, Catherine
Abstract : Background: The human intestinal microbiota exerts beneficial or harmful effects in several disorders. Many factors, including alcohol consumption, may influence its composition and trigger bacterial translocation. Excessive alcohol consumption increases gut permeability and translocation of endotoxin into peripheral circulation. Although plasma endotoxin concentrations have been measured often, quantitative changes following alcohol withdrawal have never been described in subjects with alcohol use disorder (AUD). The aim of this study was to measure microbial translocation (MT) and gut permeability markers in patients with AUD, to compare these markers to healthy controls (HC) and to monitor markers during the first 6 weeks of abstinence. Methods: Sixty‐five patients with AUD and hospitalized for alcohol withdrawal were included. Epidemiological, clinical, biological, and addictological data were gathered. Blood samples were collected at baseline, then 3 and 6 weeks after alcohol withdrawal. A hundred healthy volunteers were used as controls. Three markers of MT were monitored in plasma samples: sCD14 and lipopolysaccharide‐binding protein (LBP) were quantified using ELISA, and 16S rDNA was quantified using real‐time polymerase chain reaction. Zonulin and intestinal fatty acid binding protein (I‐FABP) blood levels were also monitored as indirect markers of gut permeability, using ELISA. Results: At baseline, LBP, 16S rDNA, sCD14 and I‐FABP markers were significantly higher in patients with AUD than in HC. Six weeks after alcohol withdrawal plasma levels of sCD14 and LBP decreased significantly. Cannabis consumption and body mass index (BMI) before alcohol withdrawal influenced baseline MT levels and the decrease in MT markers after 6 weeks. Finally, markers of MT and gut permeability did not correlate with each other before and after alcohol withdrawal. Conclusions: Before alcohol withdrawal, MT markers were higher in patients with AUD than in HC. After 6 weeks of abstinence, an improvement in MT markers was observed. Our data suggest that there is a link between MT, its improvement, BMI, and cannabis consumption. Abstract : Excessive alcohol consumption increases gut permeability and translocation of endotoxin into peripheral circulation. Before alcohol withdrawal we measured microbial translocation (MT: sCD14, LBP, 16srDNA) and gut permeability markers (zonulin, I‐FABP) in patients with alcohol use disorder and we monitored markers during the first six weeks of abstinence. At baseline, MT markers were significantly higher in AUD patients than in HC. Cannabis consumption and BMI before alcohol withdrawal influenced baseline MT levels and their decrease after six weeks of abstinence.